Application of the HRE-S to 140 horses with trigeminal-mediated headshaking and the association of clinical signs with diagnosis, therapy, and outcome - Kloock, Tanja; Hellige, Maren; Kloock, Anke; Feige, Karsten; Niebuhr, Tobias (Frontiers in Veterinary Science, 2024)
Background: Horses with trigeminal-mediated headshaking (TMHS) demonstrate different headshaking patterns (HSP), electric shock-like jerking, signs of nasal irritation, and a pain face. The History Rest and Exercise Score (HRE-S) was developed to objectively clarify the severity of the condition in affected horses. This score considers history and severity of clinical signs at rest and exercise. The aim of this study was to assess the frequency of different clinical signs and their individual association with diagnosis, treatment, and outcome in horses diagnosed with TMHS. The clinical records of horses presented with headshaking (HS) at the Clinic for Horses, University of Veterinary Medicine Hannover, between 2006-2021 were assessed retrospectively for clinical signs, diagnosis, and treatment. A total of 140 horses were included in the study. Video recordings were evaluated using the HRE-S and compared to the score described by Talbot et al. (2013). Following discharge, owners were interviewed via telephone about the outcome. Correlations between presence and severity of clinical signs, diagnosis and outcome were evaluated. Results: The following clinical signs were significantly correlated with a higher HRE-S and grade by Talbot: HS at walk (independently of HSP) (52.9%, 74/140), increased total number of demonstrated HSP (independent of the dominant HSP) (more than one HSP per horse in 91.4%, 128/140), signs of nasal irritation (75.9%, 104/137), pain face (67.8%, 80/118), and electric shock-like jerking (77.5%, 107/138). Diagnosis and outcome do not correlate with the presence of the above mentioned clinical signs. Conclusions: The HRE-S was confirmed as a valid tool to evaluate disease severity in a cohort of 140 horses with HS. Additionally, clinical signs identified as indicators for higher disease severity may have a stronger negative effect on patient welfare, but they do not correlate with diagnosis or outcome.